УПРАВЛІННЯ 3-ФАЗНИМИ МАТРИЧНИМИ ПЕРЕТВОРЮВАЧАМИ ЧАСТОТИ НА ОСНОВІ МЕТОДУ ПЕРШИХ ГАРМОНІК У ПРОСТОРІ З ДВОМА ФУНКЦІЯМИ ЧАСУ - Коротеєв, І.Є.; Клитта, М. (Інститут електродинаміки НАН України, Київ, 2012)
A procedure for the synthesis of control signals for three phase matrix frequency converters is presented. The procedure is based on extension of the space of one time variable to the space with two time variables. An expansion of control signals in Fourier series is use. References 2, figure 1.